(untitled) (Malaysian Management Journal, 2003)
It is argued that information technology can increase cost efficiency of banks by offering opportunities to substitute across inputs into production – for example, to substitute computer technology and information networks for labor. Hence, the transition to a knowledge-based financial sector would lead to banks becoming more competitive, more cost effective and better able in managing risks. As such, those banks that failed to make this transition are less able to compete as they lack the capability to innovate and face higher delivery costs. The main objectives of this paper are to determine the impact of IT on banking efficiency and its economies of scale using a sample of Malaysian banks. To achieve these objectives, stochastic cost frontier method is employed to estimate bank efficiency and panel data approach were used to examine the impact of IT on bank efficiency. The results indicate that the impact of IT on bank efficiency increases with increase in bank size, hence further supporting the process of bank mergers that are currently undertaken in the Malaysian banking industry.